Wage structure effects of international trade: evidence from a small open economy - Philip Du Caju; François Rycx; Ilan Tojerow (European Central Bank (ECB), 2011)
In the last decades, international trade has increased between industrialised countries and between high- and low-wage countries. This important change has raised questions on how international trade affects the labour market. In this spirit, this paper aims to investigate the impact of international trade on wage dispersion in a small open economy. It is one of the few to: i) use detailed matched employer-employee data to compute industry wage premia and disaggregated industry level panel data to examine the impact of changes in exports and imports on changes in wage differentials, ii) examine the impact of imports according to the country of origin. Looking at the export side, we find a positive effect of exports on the industry wage premium. The results also show that import penetration from low–income countries has a significant and negative impact on the inter-industry wage differentials, while imports from high-income countries seem to have a more ambiguous impact on the wage structure. The results suggest that trade with low-income and high-income countries has different effects on the inter-industry wage differentials.
Keywords: F16; J31; 330; inter-industry wage differentials; international trade; matched employer-employee data; Wage Structure; Lohnstruktur; Branche; Internationale Wirtschaft; Export; Import; Kleine offene Volkswirtschaft; Schätzung; Belgien